2012
DOI: 10.1161/hypertensionaha.111.188532
|View full text |Cite
|
Sign up to set email alerts
|

Visinin-Like 1 Is Upregulated in Aldosterone-Producing Adenomas With KCNJ5 Mutations and Protects From Calcium-Induced Apoptosis

Abstract: Abstract-Visinin-like 1 (VSNL1) is upregulated in aldosterone-producing adenomas (APAs) compared with normal adrenals. We demonstrate that VSNL1 overexpression in adrenocortical carcinoma cells (NCI H295R) upregulates basal and angiotensin II-stimulated CYP11B2 gene expression 3.2-and 1.5-fold, respectively. Conversely, silencing VSNL1 by RNA interference decreases angiotensin II-stimulated CYP11B2 expression and aldosterone secretion by 41.0% and 34.5%, respectively. Mutations in the potassium channel KCNJ5 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
55
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(60 citation statements)
references
References 21 publications
5
55
0
Order By: Relevance
“…Reflecting these phenotypes, CYP11B2 mRNA levels were significantly higher in APAs with KCNJ5 mutations than in those without. Although Boulkroun et al found no specific molecular phenotype for APAs with KCNJ5 mutations by the hierarchical clustering of transcriptome profiles from 102 APAs, higher levels of CYP11B2 mRNA in APAs with KCNJ5 mutations, similar to our results, have recently been reported by Wiilaimas et al and more recently by Seccia et al [9,33,34]. The discrepancy between the microarray analysis by Boulkroun et al and the results of the present study and previous findings may be due to ethnic differences and the preciseness of the microarray and qPCR techniques used.…”
Section: Discussionsupporting
confidence: 92%
“…Reflecting these phenotypes, CYP11B2 mRNA levels were significantly higher in APAs with KCNJ5 mutations than in those without. Although Boulkroun et al found no specific molecular phenotype for APAs with KCNJ5 mutations by the hierarchical clustering of transcriptome profiles from 102 APAs, higher levels of CYP11B2 mRNA in APAs with KCNJ5 mutations, similar to our results, have recently been reported by Wiilaimas et al and more recently by Seccia et al [9,33,34]. The discrepancy between the microarray analysis by Boulkroun et al and the results of the present study and previous findings may be due to ethnic differences and the preciseness of the microarray and qPCR techniques used.…”
Section: Discussionsupporting
confidence: 92%
“…9 Equivalent transfection rates of rat cDNAs and silencing of HAC15 ATP1A1 were confirmed by real-time TaqMan PCR.…”
Section: Cell Transfection and Gene Silencingmentioning
confidence: 89%
“…69 The involvement of the Wnt/␤-catenin pathway in the development of adrenocortical carcinomas is now well established. [72][73][74] The presence of activating mutations in exons 3 and 5 of the CTNNB1 gene, which encodes ␤-catenin, has been described in a wide variety of human cancers, including adrenocortical tumors.…”
mentioning
confidence: 99%